The Modern Money Theory in the Time of COVID-19. - Desilus, Bendreff (Revista del Centro de Investigación de la Universidad la Salle, 2021)
This paper critically analyzes the use of Modern Money Theory as a key policy to the economic recovery post covid-19. The gradual evolution of this health crisis and its economic impacts inevitably pushes fiscal and monetary policy in a new direction. In addition to price stability, monetary authorities place a priority for reducing the rate of unemployment for economic and social outcomes. In order to stabilize the economy in this unprecedented time, policy makers now face new economics challenges in term of response to the current crisis. Modern Money Theory (MMT) has become relevant in the current crisis, where money supply matters particularly for sustaining full employment as an important condition in the political economy of money. This consideration allowing us to first question the MMT logic and its effectiveness in term of interventionist state that stabilize the economy. The core theoretical concept of MMT is that government can finance social public needs with money financed deficits, specifically when the economy is away from the full employment.